Wojny graniczne: translacja i konwergencja w polityce i mediach - Mitchell, William J. T. (Artium Quaestiones, 2024)
The text is a translation of W. J. T. Mitchell’s essay included in his book Image Science. Iconology, Visual Culture, and Media Aesthetics (2015). It is an extensive, cultural reflection on the notion of borders and boundaries in terms of their diverse meanings, functions and interactions that take place across borders. Borders are treated as bot physical boundaries and virtual or imaginary divisions, addressed here in the sphere of geopolitics and media. The axis of his discussions are notions of translations and convergence as dynamic, productive and destructive, war or war-like interactions governed by different structures of power. This is what the scholar calls border wars. Mitchell’s examples include the Israeli-Palestine and North and South Korean borders, divisions and tensions between language and images. He concludes with an analysis of a film – John Frankenheimer’s The Manchurian Candidate (1962) – and the Showtime television series Homeland (2011–2020), where he investigates virtual, ideological border wars generated in the Cold War and war on terror periods.